Mechanical properties and short-term performance of sulphate resistance of effective microorganisms-fly ash geopolymer concrete - Harun, Mohd. Safwan (2019)
This project presented an assessment into the mechanical properties and short-term performance of geopolymer concrete prepared using fly ash in addition of Effective Microorganisms (EM) along with alkaline activators when exposed to 5% of Sodium Sulphate for up to 56 days. EM for concrete were being produced locally and used in the construction industry to promote sustainability and green concrete. EM technology was initially formulated to enhance the growth of plants in the agricultural industry and disaster treatment which the process will not produce harmful substances. Previous studies found that EM in Ordinary Portland Cement (OPC) concrete improved the concrete strength and also durability. In this research, the compressive strength of EM-fly ash geopolymer with different EM proportions in the increment of 0% (as control sample), 5%. 10% and 15%, replacing the water content were carried out at 7,14 and 28 curing days to obtain the optimum dosage of EM. Then, the strength obtained was compared to decide the ultimate trial mix before preparing cubes, cylinders and prisms for further assessment purposes. The performance of EM-fly ash geopolymer concrete were compared and discussed to what extent EM-fly ash geopolymer was able to enhance the mechanical properties of concrete. The finding shown that when adding 10% of EM into the fly ash geopolymer concrete, the compressive, density, modulus elasticity, tensile and flexural strength, were slightly contributed to the strength development respectively. Therefore, the study concluded that the optimum percentage of EM added into the fly ash geopolymer concrete was 10% in which enhancing its mechanical properties in a more sustainable, environmental-friendly and obtainable. Furthermore, the presence of EM gave a positive behavior in terms of water absorption and had a better resistant against sulphate attack compared to the fly ash geopolymer with 0% addition of EM at the ages of 14, 28 and 56 days.